On the Fauna of Cossidae (Lepidoptera) of Zimbabwe with description of a new species - Yakovlev, Roman V.; Lenz, Jürgen (Zootaxa, 2013)
The annotated list of Cossidae of Zimbabwe consists of 15 species in 9 genera from the subfamilies Cossinae and Zeuzerinae. The species Brachylia vukutu Yakovlev & Lenz, sp. nov. is newly described.